Designing culturally-rich local games for mathematics learning - Elly Susanti; Nur Wiji Sholikin; Marhayati Marhayati; Turmudi Turmudi (Beta: Jurnal Tadris Matematika, 2020)
[English]: This study aimed to design and implement local games-based mathematics learning (das-dasan) to support students' mathematical strategic competence. It consisted of three stages, namely the identification and analysis of traditional game, the design of learning activities based on Realistic Mathematics Education (RME), and the implementation in the classroom which involved twenty 7th-grade students. Data about the local game was collected through observations and interviews with five residents where the game is originated. Data on students’ strategic competence was achieved through a test given to the students after learning. The analysis of test results refers to the indicators of mathematical strategic competence. The present study found that fifteen students are able to achieve all indicators (formulating, representing, and solving the problems) with high scores. Meanwhile, five students could only represent the problems but have not fulfilled the last two indicators. The findings of this study indicate that learning mathematics based on traditional the das-dasan games has a potential to help students develop mathematical strategic competence. Keywords: Learning design, Ethnomathematics, Local game, Das-dasan, RME [Bahasa]: Penelitian ini bertujuan merancang dan mengujicoba pembelajaran matematika berbasis permainan tradisional (das-dasan) sebagai upaya untuk mengembangkan kompetensi strategis matematis siswa. Penelitian ini terdiri dari tiga tahap, yaitu: identifikasi dan analisis permainan tradisional, perancangan pembelajaran berbasis permainan tradisional berdasarkan Realistic Mathematics Education (RME), dan implementasi dalam pembelajaran di kelas yang melibatkan 20 siswa kelas VII. Data terkait permainan tradisional dikumpulkan melalui pengamatan dan wawancara dengan lima warga tempat permainan tersebut berasal. Data kemampuan strategis matematis siswa diperoleh melalui tes yang diberikan setelah pembelajaran. Analisis hasil tes siswa merujuk pada indikator kompetensi strategis matematis siswa. Hasil penelitian menunjukkan 15 siswa berhasil memenuhi semua indikator kompetensi strategis matematis dengan kategori nilai akhir sangat baik. Sedangkan 5 siswa berhasil mencapai indikator pertama (merumuskan masalah) namun belum semua memenuhi indikator merepresentasikan dan menyelesaikan masalah. Temuan penelitian ini menunjukkan bahwa pembelajaran matematika berbasis permainan tradisional das-dasan memiliki potensi untuk membantu siswa mengembangkan kemampuan strategis matematis. Kata kunci: Rancangan pembelajaran, Etnomatematika, Permainan lokal, Das-dasan, RME